Quality of the carcass in genetically improved pigs, lodged in outdoor finishing yards (Semiárida, 2020)
Two groups of barrows of a genetically improved herd (A) and another one of a non improved (B), were controlled. The purpose of this work was to evaluate the carcass yield through the parameters: percentage (%) of lean tissue, backfat thickness and dressing percentage. Also, was to assess the association between the dressing percentage with the lean tissue percentage and backfat thickness in the improved groups. Barrows were fed from 50 kg live weight (l.W.) to slaughter 102 kg l.W., during 70 days into concrete housing in four groups of 3) pigs each. AII groups were fed ad-Iibitum with 14% crude protein (C.P.), 3.100 Kcal. digestible energy at kilogram (DElkg); 0.75% Ca; 0.50% P and 0.83% Iisine. The average results showed slgnlficant differences between treatments on measured parameters. Dressing percentage (p
Keywords: Growing-finishing pigs; carcass quality; improved herd